2012
DOI: 10.1007/s12013-012-9466-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-native States of Bovine Beta-Lactoglobulin Induced by Acetonitrile: pH-Dependent Unfolding of the Two Genetic Variants A and B

Abstract: Acetonitrile (ACN)-induced unfolding of the beta-lactoglobulin variants A and B was investigated at pH 2.0, 7.0 and 9.0. ACN caused α-helix induction at low concentrations but lead to major conformational alterations when the concentration was raised. ACN also induced a concentration-dependent increase in the surface hydrophobicity of both the variants. Induction of α-helical structure and exposure of hydrophobic patches were, however, somewhat more pronounced in case of variant B, whereas the loss of tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…This may suggests that a less acidic pH solution provides a more suitable environment to enhance interactions between a-La and Lys (Jindal & Naeem, 2013). Naqvi et al (2013) studied the intrinsic fluorescence of b-lactoglobulin and claimed that, at pH 9.0, the protein showed higher fluorescence intensity than at pH 7.0, while Diniz et al (2014) found higher fluorescence intensity at pH 6.5 than at pH 3.5, which agrees with our data. These results, together with those obtained by CD, confirmed that association between a-La and Lys occurs under the conditions analyzed here, and that such association is affected by pH, temperature and heating time.…”
Section: Fluorescence Spectroscopysupporting
confidence: 90%
“…This may suggests that a less acidic pH solution provides a more suitable environment to enhance interactions between a-La and Lys (Jindal & Naeem, 2013). Naqvi et al (2013) studied the intrinsic fluorescence of b-lactoglobulin and claimed that, at pH 9.0, the protein showed higher fluorescence intensity than at pH 7.0, while Diniz et al (2014) found higher fluorescence intensity at pH 6.5 than at pH 3.5, which agrees with our data. These results, together with those obtained by CD, confirmed that association between a-La and Lys occurs under the conditions analyzed here, and that such association is affected by pH, temperature and heating time.…”
Section: Fluorescence Spectroscopysupporting
confidence: 90%
“…This observation suggests that the less acidic pH solution provides a more suitable environment for the structures when they are exposed to higher temperatures for a longer time. Naqvi et al (2013) studied the intrinsic fluorescence of β-lactoglobulin and observed that at pH 9.0, the protein showed higher fluorescence intensity than at pH 7.0, in accordance with our results. Fig.…”
Section: Fluorescence Spectroscopysupporting
confidence: 88%
“…Some aggregation was observed in purified β-LG, which could be explained by interactions with the acetonitrile in the HPLC eluent used (Chen et al, 2007;Dhamole et al, 2010). Acetonitrile can induce structural changes in the β-LG genetic variants, A and B at pH 7, such as aggregation and unfolding (Naqvi et al, 2013). In our CD spectra, the content of β-sheet was lowest in untreated β-LG.…”
Section: Discussionmentioning
confidence: 66%
“…The native variants A and B of β-LG, with a predominantly β-sheet structure, showed an intense negative band at 216 nm (Dong et al, 1996). As the acetonitrile concentration was increased, the CD spectral signature was noticeably transformed from β-sheet to typical α-helix structure (Naqvi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%